Phonetic games and traditional methods of teaching phonetics as a means of developing cognitive universal learning activities in primary school pupils: a comparative study - Abumalik Mutallievich Dedakhanov (Science and Education, 2026)
This study aims to evaluate the effectiveness of game-based phonetic methods compared to traditional phonetics teaching methods in elementary school Russian language lessons. A total of 495 students from Andidzan, Fergana, and Namangan participated in the experiment. Participants were divided into two groups - an experimental group and a control group. Analysis of the results revealed a significant advantage in phonetic knowledge among children who learned through game-based activities. Furthermore, the use of phonetic games contributed to the development of a sustained interest in learning and increased student engagement in the classroom.